Clinical simulation in health education: a systematic review - Alonso-Peña, Marta; Álvarez Álvarez, Carmen (Investigación y Educación en Enfermería, 2023)
Objective. To summarize the most recent scientific evidence on the usefulness and implementation of simulation training programs for health science students. Methods. A search and systematic review were conducted of the literature through the use of the PRISMA guidelines using the terms MESH Simulation AND healthcare AND Professional Training, including 42 articles. Results. The bibliometric analysis revealed that most of the studies were local in nature, that is, conducted in a single center, or in a few centers in the same region, from the English-speaking world, and using a mixed methodology with pre/post-test measurements. As for the educational aspects, most of the studies were conducted at universities or in the area of continuous education, used multidisciplinary teams as the student target, and used role-playing games as the simulation method. Also, these programs were especially successful in the acquisition of competencies, such as teamwork, communication, and trust. Conclusion. Clinical simulation is a teaching methodology implemented in the last twenty years, mainly in English-speaking countries; it utilizes techniques for its execution and assessment that have been validated in contrasted in many scientific studies, and lastly, it was also observed that it is useful for providing training on general competencies for multidisciplinary groups.